The use of antibiotics in acute oral health patients presenting at public dental clinics in the Western Sydney region. (15th June 2022) - Nguyen, Stephanie; Ahmed, Lamis; Villarosa, Amy; George, Ajesh; Yaacoub, Albert
Abstract: Background: There is a limited need for antibiotics when treating oral health problems, yet they are often prescribed, increasing risk of antimicrobial resistance (AMR). With AMR a threat to public health, the objectives of this study were to assess the frequency, suitability, and factors associated with antibiotic prescriptions for acute dental problems across Greater Western Sydney public dental clinics. Methods: Patients' reason for attending, details of any antibiotics use, and the treating dental practitioner's clinical examination and diagnosis were compared to current prescribing guidelines, and logistic regression was used to identify predictors of antibiotic prescription. Results: In all, 1, 071 patients participated in the study, and 15.9% reported to using antibiotics for their dental problem. Over three-quarters obtained the antibiotics from their general medical practitioner (GMP). A high prevalence of antibiotics were not indicated for the patient's complaint (71.8%) including for those with a history of extraction, pain, or intraoral swelling, who had significantly higher odds of antibiotic prescription (OR > 9). The antibiotic type prescribed was generally suitable. Conclusions: In summary, the data suggest that the majority of antibiotics were inappropriately prescribed for the patient's dental complaints and there is a need for interventions to improve compliance with antibiotic prescribing guidelines.